2007
DOI: 10.1111/j.1574-695x.2007.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofphoPandrpoSmutants ofSalmonella entericaserovar Typhi as attenuated typhoid vaccine candidates: virulence and protective immune responses in intranasally immunized mice

Abstract: The attenuation and immunoenhancing effects of rpoS and phoP Salmonella enterica serovar strain Typhi (Salmonella typhi) mutants have not been compared. Here, three S. typhi deletion mutants (phoP, rpoS, and rpoS-phoP double mutant) are constructed and these mutants are characterized with respect to invasiveness, virulence, and protective immune response compared with wild-type Ty2. It was found that phoP and phoP-rpoS deletion mutants are less invasive to HT-29 cells than the wild-type Ty2 and the rpoS single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Expression of plasminogen activator (Pla), pesticin (Pst), and type III YOP secretion components is dependent on CRP in Y. pestis (11)(12)(13). Specifically, CRP directly stimulates the expression of Pla (11, 13), a virulence factor essential for bubonic and primary pneumonic plague (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of plasminogen activator (Pla), pesticin (Pst), and type III YOP secretion components is dependent on CRP in Y. pestis (11)(12)(13). Specifically, CRP directly stimulates the expression of Pla (11, 13), a virulence factor essential for bubonic and primary pneumonic plague (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…CRP senses the switch of catabolites, and glucose may be the only free sugar that the bacteria can detect in hosts, whereas the presence of glucose stops the CRPcAMP machinery (10). Both PhoP and CRP are global regulators controlling complex cellular pathways, including multiple virulence determinants in Y. pestis (5,(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…While the role of rpoS in the S. Typhi virulence has not been explored extensively, studies have shown that rpoS gene might be involved in the S. Typhi virulence as the RpoS -strains of S. Typhi are less cytotoxic and survive better inside the resting THP-1 macrophages without induction of apoptosis than RpoS + strains [63]. A mutation in rpoS renders S. Typhi less cytotoxic to THP-1 macrophages and although the mutants survive similarly as in wild-type strain; the mutants were less invasive to epithelial cells [64]. Recent studies indicated that the allelic state of the rpoS gene and over-expression of Vi antigen are correlated.…”
Section: Regulation Of VI Polysaccharide Synthesismentioning
confidence: 99%
“…Mutants with a double knockout of the RpoS and PhoP/PhoQ show decreased virulence and decreased invasion of host cells (Lee et al, 2007). It has even been suggested that because of their inability to cause lasting infections, these double knockouts should be used to make a Salmonella vaccine (Lee et al, 2007).…”
Section: Sigma Factors and Other Regulatory Mechanismsmentioning
confidence: 99%